2013
DOI: 10.1155/2013/407875
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Regurgitation: A Severe Complication following Left Ventricular Biopsy 15 Years after Heart Transplantation

Abstract: A 71-year-old male patient underwent orthotopic heart transplantation in 1995. Due to left heart catheterization 15 years later, biopsy from the left ventricular apex was performed for rejection screening. Two days later, echocardiography revealed severe mitral valve regurgitation requiring mitral valve replacement. This is a very rare case showing that left heart biopsy may lead to severe hemodynamic complications with the need for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Vollroth et al [56] 2013 Case report Zanuttini et al [30] 2013 Case report Elhenawy et al [28] 2012 Case report…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vollroth et al [56] 2013 Case report Zanuttini et al [30] 2013 Case report Elhenawy et al [28] 2012 Case report…”
Section: Patient Demographicsmentioning
confidence: 99%
“…Margale et al [35] 2017 1 TAVR 0/1 0 Stephens et al [55] 2017 1 Aortic root replacement with AVR (bioprosthetic) NR Kyranis et al [34] 2016 1 TAVR 0/1 0 Gopalamurugan et al [41] 2014 1 TAVR 0/1 0 Holmes et al [6] 2014 3 TVR (1 mechanical, 2 bioprosthetic) 2 TV repair 1 MVR (bioprosthetic) 1 MV repair 4 Bentall 1/10 10 Unic et al [29] 2013 1 AVR (bioprosthetic) NR Vollroth et al [56] 2013 1 MVR (bioprosthetic) 0/1 0 Zanuttini et al [30] 2013 1 TAVR NR Elhenawy et al [28] 2012 1 Aortic root replacement NR Bruschi et al [37] 2010 1 TAVR 0/1 0 Goerler et al [19] 2010 15 TVR (bioprosthetic) 5 TV repair 2 MVR (not reported on type) 1 MV repair 1 David 3 Aortic root replacement 2 AVR 13/25 52.00…”
Section: Diagnosismentioning
confidence: 99%